The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.jasms.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “intensity fading” phenomenon in the study of noncovalent interactions by MALDI-TOF mass spectrometry

Abstract: The difficulties to detect intact noncovalent complexes involving proteins and peptides by MALDI-TOF mass spectrometry have hindered a widespread use of this approach. Recently, "intensity fading MS" has been presented as an alternative strategy to detect noncovalent interactions in solution, in which a reduction in the relative signal intensity of low molecular mass binding partners (i.e., protease inhibitors) can be observed when their target protein (i.e., protease) is added to the sample. Here we have perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 49 publications
(38 reference statements)
3
28
1
Order By: Relevance
“…Similar conclusions were reached in the study of protease inhibitor complexes (Yanes et al, ). The investigation of the effects of different matrix solutions at different pH, with and without the use of thin layer deposition, on the stability of two protease inhibitor complexes, and thus the relative intensity of the ligand, was largely unaffected by pH in the range of 2.5–5.5 (Yanes et al, ) but could be disrupted below this pH range.…”
Section: Key Conditionssupporting
confidence: 85%
“…Similar conclusions were reached in the study of protease inhibitor complexes (Yanes et al, ). The investigation of the effects of different matrix solutions at different pH, with and without the use of thin layer deposition, on the stability of two protease inhibitor complexes, and thus the relative intensity of the ligand, was largely unaffected by pH in the range of 2.5–5.5 (Yanes et al, ) but could be disrupted below this pH range.…”
Section: Key Conditionssupporting
confidence: 85%
“…Recent studies have suggested that the specific interactions between proteins and their peptide ligands could be deduced using IF-MALDI-MS, namely, introduction of a protein receptor could result in a selective decrease of the ion abundances of its peptide ligands compared with the nonbinding control [25][26][27][28][29][30][31][32][33][34].…”
Section: Detection Of the Calmodulin-peptide Interactions Using If-mamentioning
confidence: 99%
“…When the signal intensity reached the saturation point, further increase of the laser intensity made the fading phenomena less pronounced and it was difficult to discriminate the target peptides with the nonbinding control. Besides these instrumental parameters, the influence of analyte concentration on the fading phenomena was also investigated because previous studies suggested that the analyte concentration might have an impact on the observed fading [34]. Peptide mixtures containing the target peptide at desired concentrations were incubated with equal amount of calcium-saturated calmodulin (1:1 M), followed by the addition of matrix solutions.…”
Section: Detection Of the Calmodulin-peptide Interactions Using If-mamentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of non‐covalent interactions was demonstrated a few years after the introduction of MALDI MS,5 e.g. antibody–antigen interactions;5–9 intensity fading where the ion intensity from a ligand is suppressed in the presence of a binding protein;10, 11 three‐dimensional biochip fabrication using methacrylate polymers, where proteins are immobilized followed by incubation with appropriate ligands9 and desorption/ionization on porous silica (DIOS), which has been used for functional characterization and identification of small biomolecules without use of matrix 12, 13. The general applicability of these methods is dependent on ease of use and sensitivity.…”
Section: Introductionmentioning
confidence: 99%